2017
DOI: 10.1080/14737167.2017.1375406
|View full text |Cite
|
Sign up to set email alerts
|

The projected public health and economic impact of vitamin D fortified dairy products for fracture prevention in France

Abstract: The potential public health and economic benefits of vitamin D fortified dairy products is expected to substantially increase in the future, especially in the population aged over 80 years. Decision makers should be aware of the current and future potential benefits of dairy products to protect bone fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…With reference to vitamin D food fortification, there are only a few reports available on its cost-effectiveness. The available studies have reported that systematic vitamin D fortification may indeed be highly cost-effective [102]. The following distribution of costs for a typical food fortification programme was determined as follows: 80% recurrent production costs, 8% marketing and education costs, 7% food control and monitoring costs, and 5% other production costs [103].…”
Section: Vitamin D Fortification Strategiesmentioning
confidence: 99%
“…With reference to vitamin D food fortification, there are only a few reports available on its cost-effectiveness. The available studies have reported that systematic vitamin D fortification may indeed be highly cost-effective [102]. The following distribution of costs for a typical food fortification programme was determined as follows: 80% recurrent production costs, 8% marketing and education costs, 7% food control and monitoring costs, and 5% other production costs [103].…”
Section: Vitamin D Fortification Strategiesmentioning
confidence: 99%
“…Previous scenario analyses have modeled changes in healthcare costs from beneficial shifts in dietary patterns and provide an indication of the potentially substantial economic impact associated with modifications to the population's diet [7][8][9][10][11]. The purpose of this study is to estimate the impact on healthcare costs associated with a reduced incidence of total CVD based on modeling incremental increases in whole grains consumption as a proportion of total grains up to levels recommended in the DGA.…”
Section: Introductionmentioning
confidence: 99%
“…This new policy would require formal Government approval and careful modelling of the current level of vitamin D intake taking into account voluntary fortification and self-supplementation. However, it could have significant benefits in terms of bone and musculoskeletal health (economically and socially) [43][44][45] in addition to the suggested immune health benefits. Moreover this is particularly timely given current lock-down arrangements and government advice e.g.…”
Section: Discussionmentioning
confidence: 99%